CRITICAL AND CREATIVE AWARENESS SCHOOL TEATER ACTORS - Indra Suherjanto (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2020)
Theater at school is an extra-curricular activity. It is hoped that theater arts in the school will bring forth qualified young actors as professional actors. Theater actors in schools that develop into professional actors must have abilities that are equivalent to professional actors. Theater actors in schools must have proper theater skills. The Augusto Boal theater concept is a theater method that can be used as a process of awareness, liberation in developing aspects of life, sensitivity and creative power and imagination. The Boal concept is oriented to the process of empowering knowledge that is aware of life values and liberation and develops a critical attitude. Critical awareness is needed for theater actors to be able to open insight into thinking, create space to freely identify and analyze. Andre Malraux in Alma Hawkins explains that a person's creative journey involves seeing, exploring and realizing. Creative starts from the desire to realize a form of art. The creativity of theater will be achieved by seeing, exploring, and realizing what is in man by feeling and absorbing it and then realizing it by free thinking. In order for a theater actor in a school to develop and make it possible to become a professional actor, it is important to have critical and creative awareness in theater.